COVID-19 Related Knowledge and Mental Health: Case of Croatia - Galić, Marko; Mustapić, Luka; Šimunić, Ana; Sić, Leon; Cipolletta, Sabrina (Frontiers in Psychology, 2020)
Background and aims: COVID-19 pandemic has led to radical and unexpected changes in everyday life and people’s psychophysical health has been affected. This study examined the relationship between COVID-19 related knowledge and mental health in a Croatian sample of participants. Methods: An online survey was conducted from March 18th until March 23rd, 2020 and a total of 1244 responses were collected. 85.5% of participants were women and the majority of the participants completed secondary education (58.4%). Measures included eight questions regarding biological features of the virus, symptoms, and prevention, the Hospital Anxiety and Depression Scale (HADS), and Optimism-Pessimism Scale (OPS). According to the answers given on each question on COVID-19 related knowledge, participants were divided in two groups (informed and uninformed) and compared in the expressed levels of anxiety, depression, pessimism, and optimism. Full mediation models for questions about handwashing and ways of transmission were estimated. Results: Participants who responded correctly on the question about handwashing had higher levels of anxiety, depression, and pessimism than those participants whose answer was incorrect, while participants who answered correctly on the question about percentage of patients who develop serious breathing problems had higher levels of depression than those who answered wrong. Lower levels of anxiety and pessimism were observed in the participants who answered correctly about ways of transmission. Higher levels of pessimism were found in the participants who scored incorrectly on questions about the efficiency of antibiotics, most common symptoms, and the possibility of being infected by asymptomatic carriers. No differences between observed variables were found for questions about the efficiency of regularly rinsing the nose, and the virus time of survival on surfaces. Higher levels of knowledge about handwashing were predicted by higher levels of anxiety and pessimism. Higher levels of knowledge about ways of transmission were predicted by lower levels of anxiety and lower levels of pessimism. Conclusions: The findings of this study suggest that knowledge about COVID-19 may be useful to reduce anxiety and depression, but must be directed to the promotion of health behaviors and to the recognition of fake news.